2007
DOI: 10.2105/ajph.2005.078113
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Intimate Partner Violence and Related Injuries Among Women in Yokohama, Japan

Abstract: We estimated rates of intimate partner violence and related injuries in a sample of 1371 women aged 18 to 49 years in Yokohama, Japan. By the age of 30 years, 14.3% of women who had ever had a partner had experienced violence from that partner, and 3.3% had suffered injuries related to such violence. By the time women had reached the age of 49 years, these percentages were 19% and 4%, respectively. In addition to the need for increased prevention efforts, our findings indicate the need for an expanded legal de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 3 publications
1
12
0
Order By: Relevance
“…Nevertheless, it is quite higher than when it compared with a study conducted in 8 South African countries indicated that partner physical violence ranged lowest rates from 9% in Mozambique and Malawi to the highest (32%) in Zambia [18]. It has significant difference as compared to study finding from South Africa, Japan (Yokohama) and in Brazil revealed that 1–4 in every 10 women had experienced physical intimate partner violence at some point in their past [13,17,19]. The difference might be presence of culture and traditional gender norms that support wife beating within the community.…”
Section: Discussionmentioning
confidence: 89%
“…Nevertheless, it is quite higher than when it compared with a study conducted in 8 South African countries indicated that partner physical violence ranged lowest rates from 9% in Mozambique and Malawi to the highest (32%) in Zambia [18]. It has significant difference as compared to study finding from South Africa, Japan (Yokohama) and in Brazil revealed that 1–4 in every 10 women had experienced physical intimate partner violence at some point in their past [13,17,19]. The difference might be presence of culture and traditional gender norms that support wife beating within the community.…”
Section: Discussionmentioning
confidence: 89%
“…This prevalence is similar to those reported in a hospital-based study in Baghdad (58%) [14], primary health care centers in Madina, Saudi Arabia (57.8%) [9], Sivas, Turkey (52%) [15], Eastern India (56%) [16] and Jahrom, Iran (64.7%) [17]. This prevalence is considerably higher than the rates reported among women attending general practice in some other countries and cities such as Japan (14.3%) [18], Norway (26.8%) [19], China (43%) [20], Esfahan, Iran (36.8%) [21] and Ireland (39%) [22]. The wide discrepancies in prevalence of violence may reflect different definitions for violence in every society, the method of screening, religious beliefs and cultural issues [23].…”
Section: Discussionmentioning
confidence: 99%
“…Studies designed to measure the frequency and identify the determinants of IPV focus mostly on women as victims (Bonomi et al 2009;Garcia-Moreno et al 2006; Thompson et al 2006;Yoshihama et al 2007). However, a review of 91 studies showed that one in five men was a victim of IPV (Desmarais et al 2012a) and poor health outcomes have been associated with male victimization (Reid et al 2008).…”
Section: Introductionmentioning
confidence: 99%